Epidemiological and molecular approach to determine factors associated with diarrheagenic E. coli in food for children under five in Mozambique - Buys, E.M. (Elna Maria) (University of Pretoria, 2025)
Thesis (PhD (Microbiology))--University of Pretoria, 2025.